The Effects of Different Cotton Varieties on the Growth and Feeding Preferences of Helicoverpa armigera - Lei Yue; Xuehua Shao; Jianhao Dong; Guoyi Xia; Xiang Yan; Aizimaitijiang Tuerxun; Wei Lu (Insects, 2025)
Xinjiang is an autonomous province in northwest China [...]